2013
DOI: 10.1039/c3cp53089b
|View full text |Cite
|
Sign up to set email alerts
|

A device for measuring spin selectivity in electron transfer

Abstract: A new type of device is presented that allows direct measurement of spin selectivity in charge transfer processes occurring in adsorbed molecules. The new device provides direct information about the nature of the charge being transferred (electrons or holes) and on spin selectivity, if it exists. Here the device is applied for establishing the spin-dependent electron transfer through double-stranded DNA and its variation with the length of the oligomer. The DNA is self-assembled on a silver substrate and is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…[20,21] The robust PSI, used in these experiments, is isolated from the thylakoid membranes of cyanobacteria and is stable and active when adsorbed in a dry environment. [22] The spin selectivity of the ET process and its temperature dependence were studied by applying a new type of capacitance device [23] (see Figure 1 B-D, and details in SI).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21] The robust PSI, used in these experiments, is isolated from the thylakoid membranes of cyanobacteria and is stable and active when adsorbed in a dry environment. [22] The spin selectivity of the ET process and its temperature dependence were studied by applying a new type of capacitance device [23] (see Figure 1 B-D, and details in SI).…”
mentioning
confidence: 99%
“…The values obtained for the polarization, at room temperature, are extremely high and exceed those measured for ET through 78 base long DNA with the same device. [23] The correction procedure, as described in the SI has two parameters, the nonideal spin polarization of the nickel and the silvers Debye temperature. While the error in the first parameter is very small, the actual Debye temperature may vary from sample to sample by about 10 %, as probed in ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 The robust PSI, used in these experiments, is isolated from the thylakoid membranes of cyanobacteria and is stable and active when adsorbed in a dry environment 22. The spin selectivity of the ET process and its temperature dependence were studied by applying a new type of capacitance device23 (see Figure 1 B–D, and details in SI).…”
mentioning
confidence: 99%
“…Recent experiments on spin transport along DNA molecules have led to an important breakthrough in molecular spintronics [1][2][3]. Göhler et al reported that the electrons transmitted through self-assembled monolayers of double-stranded DNA (dsDNA) at room temperature were highly polarized and that the spin polarization increased with the DNA length, while spin-dependent effects were not observed in single-stranded DNA (ssDNA) monolayers [1].…”
Section: Introductionmentioning
confidence: 99%